Hong Kong's National Security Law: A Socialist Legal Transplant?. (3rd March 2022) - Pascoe, Daniel
Abstract: The recently enacted Law of the People's Republic of China on Safeguarding National Security in the Hong Kong Special Administrative Region (NSL) is unique in global perspective: it was both drafted by and adopted from a jurisdiction espousing an entirely different type of legal system. In this article, I consider the NSL as a potential socialist legal transplant from the People's Republic of China to its Special Administrative Region of Hong Kong upon its promulgation in June 2020. I consider why, in the criminal law context, the NSL bears certain socialist characteristics and may even be classified as a socialist law. I also consider whether the NSL might be the world's first ever socialist criminal law transplant into a common law jurisdiction, and discuss what this might mean for legal interpretation and comparative law scholarship more generally. While existing comparative law scholarship on legal transplants has focused, where relevant, on transplants into States espousing socialist legal systems or between such systems, rarely have scholars encountered and analysed laws making their way across legal boundaries in the other direction. This article uses the example of the NSL, enacted by the Standing Committee of the National People's Congress in Beijing and applied to Hong Kong's common law legal system, to begin to fill the gap.